A Study On Breast Cancer Cognizance And Its Linkages To Social Work (International Journal of Food and Nutritional Sciences, 2022)
The attempt of this study was focused on highlighting and analyzing the knowledge and awareness on theme of understanding of breast cancer as a disease and associated risk factors by university students in two institutes of Kangra district of Himachal Pradesh. The study was conducted on 100 college students using questionnaire and responses was collected. The study investigates the perception of students on breast cancer. Also, it establishes the linkages with Social work Profession to help the patients in their time of emergencies. The study also successfully established that the educative and sensitization themes on breast cancer especially among younger population can help in enhancing the knowledge base for the cause of early detection of symptoms.